AKTIVITAS ANTIBAKTERI SENYAWA GOLONGAN TRITERPENOID DARI BIJI PEPAYA (Carica papaya L.) - I M. Sukadana; Sri Rahayu Santi; N. K. Juliarti (Program Studi Kimia, FMIPA, Universitas Udayana (Program of Study in Chemistry, Faculty of Mathematics and Natural Sciences, Udayana University), Bali, Indonesia, 2008)
Isolation, identification, and antibacterial activity examination have been conducted for triterpenoidscompounds of carica papaya L. Maseration of 500 g pawpaw seed powder in n-hexane gave 21.66 g extract whichreacts with Liebermann-Buched reagent resulting in colour change (yellow to purple). Column chromatographyseparation of the extract resulted in 0.05 g yellow isolate (F3) which contains aldehyde triterpenoids. Infrared spectraindicated aliphatic –C-H stretching, -CH2 bending, -CH3 bending, and C=O. Ultra violet – visible spectra showedabsorption at 228.5 nm and proad peak at 287.7 nm. Antibacterial axamination showed that 1000 ppm at the isolateinhibits the growth of Escherichia coli and Staphylococcus auerus.